1973
DOI: 10.1021/ic50120a038
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-sulfur system. I. Differential thermal analysis

Abstract: Attempts to gain a better understanding of the reactive species in the sodium-sulfur battery system developed at Ford Motor Co. have led us to reexamine the sodium-sulfur phase diagram published by Pearson and Robinson in 1930. A modified phase diagram was constructed based on dta studies. In addition, dta revealed that when a mixture of Ña2S and NajSj or Ña2S4 and S8 is heated, a reaction takes place around the melting point of sulfur, with the formation of the pentasulfide, Na2Ss, as the initial step. Unless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 0 publications
3
31
0
1
Order By: Relevance
“…This finding is consistent with the immiscibility of sodium sulfides in molten sulfur at temperatures near sulfur's melting point (Rosén and Tegman 1972, Oei 1973, Tegman 1976). …”
Section: Figsupporting
confidence: 83%
“…This finding is consistent with the immiscibility of sodium sulfides in molten sulfur at temperatures near sulfur's melting point (Rosén and Tegman 1972, Oei 1973, Tegman 1976). …”
Section: Figsupporting
confidence: 83%
“…Oei (2,3) and Janz et al (4) have shown that, at temperatures greater than -100~ Na2S~ is a eutectic mixture of Na2S2 and Na2S~. Capacities were determined by dividing the ampere-hours removed during discharge by the theoretical capacity.…”
Section: Methodsmentioning
confidence: 99%
“…The phase equilibrium and the thermodynamic properties of the phases in system (Na + S) have been widely investigated [16,[31][32][33][34][35][36]. Due to experimental difficulties, a notable scatter exists for different experimental investigations.…”
Section: Na + Smentioning
confidence: 99%
“…The phase diagram has been investigated by visual-polythermal methods [34], thermal analysis [31][32][33][34], differential thermal analysis [16,34,36], quenching techniques [34] and EMF-studies [35,37]. The experimental data points are shown in figure 1.…”
Section: Na + Smentioning
confidence: 99%